The impact of nutrition education on nutritional status, physical activity and nutrition-related quality of life for university students in Terengganu - Wan Putri Elena Wan Dali
Poor eating behaviors and reduced physical activity (PA) could likely lead to the risk of osteoporosis, obesity, diabetes and cancer in later life. Eating behaviors have also been shown to be interestingly related to quality of life (QoL). Therefore, nutrition education (NE) could be useful in delivering healthy diet and nutrition information for this cohort. This three-part study was conducted to assess the 1) current body weight, eating behaviours, PA and QoL, 2) acceptability and applicability of the newly-developed NE intervention and 3) effectiveness of NE intervention on body weight, eating behaviours, PA and QoL. Part I involved the assessment of current body weight, dietary intakes, PA and QoL based on a cross-sectional pilot study among 116 university students in a public university in Terengganu. Results provided an overall evidence of unsatisfactory dietary habits and PA. Part II comprised the dissemination of the latest Malaysian Dietary Guidelines (MDG) 2010 which were delivered through three modes; 1) conventional lectures, 2) brochures and 3) text messages via short messaging system (SMS). The Malay version of Nutrition Education Tool's Evaluation Questionnaire (NETEQ) was distributed to evaluate the students' understanding on the contents, presentation and illustrations showed in the slides, brochures and text messages (n=116). Majority rated the presentation, brochures and text messages as comprehensible, interesting and good with regard to its information, pictorial graphics and language. The final part employed a longitudinal, cluster randomised study among 417 respondents from four public universities in Terengganu who were then randomly assigned to either' intervention group (IG=205) or control group (CG=212). The IG received NE while the CG did not receive any form of NE. Overall, 380 respondents (response rate=91.1 %; IG=178; CG=202) completed both baseline and follow-up (after 10 weeks). After 10 weeks, IG possessed relatively better nutrient intakes compared to CG particularly in energy, calcium, vitamin C and thiamine (p<0.05). The consumption of fruits, fruit juices, milk and dairy products, fish and eggs had also significantly improved (p<O.05) for IG. All PA patterns were also significantly increased among IG (p<O.05). Compared to general health-related QoL, significant impacts (p<O.05) on nutrition-related QoL were found in Food Impact, Physical Functioning, Social/Interpersonal and Overall NOoL domains for IG. Findings indicated that the provision of NE through a variety of modes improved their dietary habits, PA and eventually nutrition-related QoL, sUJlgesting that this innovative NE strategy needs could be widely implemented in future to target different segments of the population. Key Words: nutrition education, university students, nutritional status, physical activity, nutrition-related quality of life (QoL)